Cinnamomum verum improved the functional properties of bioyogurts made from camel and cow milks - Shori, A.B.; Baba, A.S. (2011)
The effects of Cinnamomum verum on the changes in antioxidant activities, proteolysis, total phenolic content and in vitro inhibition of α-amylase and α-glucosidase of bioyogurts prepared from cow- and camel-milks during 21 days of storage at 4 °C was investigated. The result shows that pH of cow-milk bioyogurt (cow-MY) decreased more than camel-milk bioyogurt (camel-MY) whereas, total titratable acidity increased to similar extent in both types of bioyogurts. The addition of C. verum in both type of bioyogurts enhanced the total phenolic content during the entire storage period. The antioxidant capacity of C. verum-bioyogurts was higher than plain-bioyogurts. Proteolysis was higher in camel-milk bioyogurt than cow-milk bioyogurt. The inhibition of α-amylase in fresh bioyogurts was stronger in camel-milk bioyogurt than cow-milk bioyogurt. The reverse was true for α-glucosidase. Conclusively, C. verum can enhance bioyogurt functional properties with potential therapeutic values for the diabetics.